The overall concept of phenomenological philosophy in the visual presentation (Journal of the College of Basic Education, 2022)
Since the beginning of the philosophical, analytical, aesthetic criticism of the first volumes of the drama, which was moved and occupied by Greek philosophy and its moving thought, and through time, the social intellectual structures moved through sophisticated movements, intertwined events and conflicts.